Necrotizing Sialometaplasia of Palate: A Case Report - N. G. Garcia; D. T. Oliveira; S. E. S. Faustino; A. L. R. Azevedo (Hindawi Limited, 2012)
Background. Necrotizing sialometaplasia (NS) is an uncommon benign reactive necrotizing inflammatory process involving minor salivary gland that often mimics malignancy both clinically and histopathologically. Case Report. We report the case of a healthy 26-year-old man with a painless swelling in the hard palate near the middle raphe, asymptomatic, well limited, and raised edges. The patient was submitted to incisional biopsy and histopathological examination. The histological diagnosis was necrotizing sialometaplasia. Discussion. The clinical and histological similarity between this entity and a malignant lesion implies a risk of unnecessary or mistreatment. Therefore, clinicians and pathologists should be aware of this lesion as to avoid errors in the diagnosis and treatment of this benign pathologic condition.